2019
DOI: 10.18632/aging.102071
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MIR22HG abrogation inhibits proliferation and induces apoptosis in esophageal adenocarcinoma cells via activation of the STAT3/c-Myc/FAK signaling

Abstract: Long non-coding RNAs (lncRNAs) have involved in human malignancies and played an important role in gene regulations. The dysregulation of lncRNA MIR22HG has been reported in several cancers. However, the role of MIR22HG in esophageal adenocarcinoma (EAC) is poorly understood. Loss of function approaches were used to investigate the biological role of MIR22HG in EAC cells. The effects of MIR22HG on cell proliferation wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…It was also demonstrated that Bcl-2 was downregulated and BAX was upregulated following PTTG11-siRNA transfection, showing that together, these processes are responsible for increased levels of cell apoptosis. These results are similar to previous reports (24,25).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was also demonstrated that Bcl-2 was downregulated and BAX was upregulated following PTTG11-siRNA transfection, showing that together, these processes are responsible for increased levels of cell apoptosis. These results are similar to previous reports (24,25).…”
Section: Discussionsupporting
confidence: 93%
“…A high expression level of PTTG11 has been observed in U251 glioma cells. Both STAT3 and PTTG11 have been implicated in multiple steps of glioma development and progression (19,24), but the mechanisms that regulate their coordinated functions were not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, functional experiments demonstrated that the effect of knockdown BECN1 on cancer cells was reversed by genetic or pharmacological inhibition of STAT3, strongly indicating that BECN1 is involved in CRC metastasis through regulation of STAT3 phosphorylation in CRC. Notably, numerous reports have demonstrated that STAT3 is involved not only in tumor metastasis but also in proliferation, the cell cycle and apoptosis [39][40][41] . Herein, we found that BECN1 influenced the CRC metastasis mediated by STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the biological function and underlying molecular mechanism of lncRNAs in various types of cancer, including colorectal cancer, gastric cancer, hepatocellular carcinoma, renal cell carcinoma, prostate carcinoma and EAC (11)(12)(13)(14)(15)(16)(17). Although studies reported that lncRNAs can be involved in the development and progression of ESCC (6,14), only a few studies have determined the function of lncRNAs in EAC (5,18).…”
Section: Introductionmentioning
confidence: 99%